Chemotherapy as a critical treatment modality for non-surgical metaplastic breast cancer: evidence from SEER database and clinical cohort - Wang, Pin; Fang, Huiying; Yang, Dejuan; Liu, Ying; Li, Ling; Wu, Jian (Frontiers in Oncology, 2025)
IntroductionMetaplastic breast carcinoma (MPBC) is a highly aggressive subtype of breast cancer, characterized by enhanced metastatic potential and invasive behavior. While surgery is a cornerstone of treatment, there is limited research on patients who did not undergo surgery.MethodsWe conducted a retrospective analysis of non-surgical MPBC patients using data from the Surveillance, Epidemiology, and End Results (SEER) database (1975–2019). Additionally, non-surgical MPBC patients were recruited from The Third People’s Hospital of Chengdu, The First Affiliated Hospital of Chongqing Medical University, and the Chongqing University Cancer Hospital to form the clinical validation cohort (2010–2024). We collected demographic and clinical data, including age, race, marital status, tumor location, and treatment modalities, etc. The primary endpoints were overall survival (OS) and breast cancer-specific survival (BCSS). Statistical analyses were performed using R software, with Kaplan-Meier curves and Cox regression models for univariate and multivariate analyses.ResultsA total of 92 non-surgical MPBC patients were included from SEER database. The majority were aged≥60 years (65.22%), White (76.09%), and single (64.13%). Tumors were most frequently located in the upper quadrant (32.61%). Additionally, M1 patients were more likely to receive chemotherapy and radiotherapy compared to M0 patients (50.00% vs. 36.67%; 38.46% vs. 13.33%). Cox regression analysis identified chemotherapy and M stage as significant prognostic factors. Survival analysis showed that chemotherapy significantly improved OS and BCSS (P<0.001), while radiotherapy had no significant impact on survival (P>0.05). In the clinical cohort of 30 non-surgical MPBC patients, Kaplan-Meier curves demonstrated that chemotherapy significantly prolonged patient survival (P=0.039), whereas radiotherapy did not show a significant effect on survival (P=0.309).ConclusionsFor MPBC patients who did not undergo surgery, chemotherapy significantly prolongs survival, highlighting its crucial role in treatment.